2019
DOI: 10.3390/nu11112591
|View full text |Cite
|
Sign up to set email alerts
|

Cuscutae Japonicae Semen Ameliorates Memory Dysfunction by Rescuing Synaptic Damage in Alzheimer’s Disease Models

Abstract: Alzheimer’s disease (AD) is the most common type of dementia in the elderly. It is characterized by the accumulation of amyloid-beta (Aβ) and progressive cognitive impairment. To alleviate the symptoms of AD, functional foods and nutrients have been used for centuries. In this study, we investigated whether Cuscutae Japonicae Semen (CJS), a medicinal food traditionally used in East Asia, has effects on memory improvement and synapse protection in AD. We orally administered CJS to 5x familiar AD (5xFAD) transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The MWM task was used to evaluate the spatial learning and memory abilities of mice as previously described [29]. The MWM assay consisted of four stages: pretraining (day 34), training (days [35][36][37][38], testing (day 39), and probe (day 40). The swimming ability of the mice was tested on day 34.…”
Section: Morris Water Maze (Mwm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The MWM task was used to evaluate the spatial learning and memory abilities of mice as previously described [29]. The MWM assay consisted of four stages: pretraining (day 34), training (days [35][36][37][38], testing (day 39), and probe (day 40). The swimming ability of the mice was tested on day 34.…”
Section: Morris Water Maze (Mwm)mentioning
confidence: 99%
“…Based on these data, PS128 prevented icv-STZ-induced gliosis in 3 × Tg-AD mice. Synaptic proteins, including postsynaptic density protein 95 (PSD95) and synaptophysin, play critical roles in synaptic plasticity and cognitive function [37,38]. Therefore, the levels of PSD95 and synaptophysin proteins were examined using western blot analyses.…”
Section: Ps128 Supplementation Prevented Gliosis In 3 × Tg-ad Mice Treated With Icv-stzmentioning
confidence: 99%
“…Previous studies reported that the individual components of CCL01, Cuscuta seeds and Lactobacillus paracasei NK112 (NK112), reduced the production levels of IL-6 and TNF-α and expression levels of the proteins iNOS and COX-2 via regulating NF-κB activation. 10–12,23 However, the anti-neuroinflammatory effects of the mixture with a synergic effect on LPS-induced BV2 microglia have not been reported. Thus, our data supported the anti-neuroinflammatory effects of CCL01, which was shown in our previous study to be a potential enhancer of memory function.…”
Section: Discussionmentioning
confidence: 99%
“…9 Indeed, each component showed ameliorative effects on models of neurological disorders such as depression and cognitive impairment. 10–12 Therefore, our study suggests a new focus on the microbiota–gut–brain axis with respect to the central nervous system as a new potential pathway that may mediate neurodegenerative pathogenesis ( i.e. , depression and cognitive impairment) in response to lipopolysaccharide (LPS).…”
Section: Introductionmentioning
confidence: 99%
“…plant, contains high contents of flavonoids, polysaccharides, alkaloids, and resin glycosides. Several studies have shown that CS has various biological activities pertaining to neuroprotection (Zhen et al, 2006), anti-neuroinflammation (Kang et al, 2014), the rescue of synaptic damage (Ju et al, 2019), and the alleviation of oxidative stress (Lin et al, 2018). Seok Y et al reported that CS extract suppresses the inflammatory response by inhibiting the expression of cyclooxygenase-2 (COX-2), downregulating the transcription levels of TNF-α, IL-1β, and IL-6, and contributing to the nuclear translocation of nuclear factor kappa B (NF-κB) P65 in activated microglia (Kang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%